(untitled) (Research, Society and Development, 2021)
This is a quali-quantitative study that aims to understand the objective and subjective conditions experienced by Brazilian university professors in the face of emergency remote work, in the COVID-19 pandemic. Data from 508 respondents who answered the open question of a web survey were analyzed in five Categories of Reports on Remote Working Conditions (1. Home space; 2. The change from face-to-face to remote; 3. No complaints; 4. Reflections on illness; 5. Mixed). Sociodemographic, household and working conditions data were analyzed between reporting categories using the Pearson/Fischer chi-square test. Most professors were female (65%), 40 years or older (77%), married (65%), with children (64%) and lived with up to three people (74%). The reports classified in category 2 were prevalent (42.9%) and showed difficulties in social interaction; increased demand; feeling of exploration; and lack of institutional support. There was an association with sociodemographic data, number of rooms and residents, and some conditions for teleworking (p<0.05). Women reported the fragile division between the different roles they perform. Professors with a greater number of residents at home and the older ones had more difficulties when moving from face-to-face to teleworking. Reports about illness were more frequent in females, among those who have been working for longer in teaching and without good internet connection. The emergency teleworking routine was marked by adaptations, challenges and dilemmas, which demand policies to prevent injuries and protect the health of University professors.